Article 44 of Indian Constitution: Debates and Challenges - Kumari, Kanchan (Innovative Research Thoughts, 2018)
Article 44 of the Indian Constitution states that “the State shall endeavour to secure for the citizens a uniform civil code (UCC) throughout the territory of India.” The desirability of a uniform civil code is consistent with human rights and the principles of equality, fairness and justice. After the revocation of Article 370, the central family law Acts were extended to Jammu and Kashmir. Although, this is another step towards implementing UCC throughout India, still a long distance is to be covered in this pursuit. The objective of Article 44 of the Directive Principles in the Indian Constitution was to address the discrimination against vulnerable groups and harmonise diverse cultural groups across the country. Dr. B R Ambedkar, while formulating the Constitution had said that a UCC is desirable but for the moment it should remain voluntary, and thus the Article 35 of the draft Constitution was added as a part of the Directive Principles of the State Policy in part IV of the Constitution of India as Article 44. It was incorporated in the Constitution as an aspect that would be fulfilled when the nation would be ready to accept it and the social acceptance to the UCC could be made.